Post-marketing safety surveillance of pneumococcal vaccines: a real-world pharmacovigilance study using the U.S. vaccine adverse event reporting system (VAERS) database - Zheng, Xinkuo; Liu, Meishen; Ding, Aili; Zhang, Shihong; Wu, Ling; Kong, Fanli; Sun, Weijia; Peng, Yuchen; Xi, Yalin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPneumococcal vaccines have been utilized in the United States for decades with extensive clinical safety records. However, comprehensive post-marketing pharmacovigilance evaluations for all available types remain lacking. This study aimed to assess adverse events following immunization (AEFI) using the VAERS database and analyze potential associations between adverse events (AEs) and vaccine administration based on VAERS data.MethodsWe retrieved all AEs associated with pneumococcal vaccines recorded in the VAERS database from 1990 through March 2025. Descriptive analyses were conducted to summarize the demographics, clinical characteristics, and vaccination profiles of reported cases. Disproportionality analysis was performed to detect potential safety signals between AEs and vaccine administration.ResultsThe VAERS database documented 157,244 individuals receiving pneumococcal vaccines, with 158,778 doses administered, capturing 632,481 AE reports following vaccination during the study period. Females showed higher AE reporting rates (54.29%) compared to males (36.88%), with the majority of cases (38.20%) occurring in individuals aged < 18 years. Complete recovery (44.20%) and hospitalization (14.94%) were the most common outcomes. Most AEs (77.11%) occurred within 0–30 days post-vaccination (median onset: 0 day). Pneumococcal polysaccharide vaccine (PPSV, 48.92%) and 13-valent pneumococcal conjugate vaccine (PCV13, 27.57%) constituted the predominant vaccine types. Disproportionality analysis identified 929 positive AE signals across 24 system organ classes (SOCs), with injection site erythema [reporting odds ratio (ROR) = 4.24], injection site swelling (ROR = 4.19), and injection site pain (ROR = 2.75) being the most frequent. Designated Medical Event (DME) screening revealed erythema multiforme (n = 398) and product contamination microbial (ROR = 11.25) as key safety signals. General disorders (ROR = 1.73) and skin conditions (ROR = 1.69) were the predominant SOC categories.ConclusionsThis post-marketing surveillance has revealed predominantly non-serious AEs, with most adverse events clustered within 30 days post-vaccination. These observations reinforce the established safety profile of pneumococcal vaccines while emphasizing temporal risk patterns to guide post-vaccination monitoring protocols and risk-benefit evaluations.